Association of personality profiles with depressive, anxiety, and cancer-related symptoms in patients undergoing chemotherapy. (15th October 2017) - Morgan, Stefana; Cooper, Bruce; Paul, Steven; Hammer, Marilyn J.; Conley, Yvette P.; Levine, Jon D.; Miaskowski, Christine; Dunn, Laura B.
Abstract: Background: This study identified latent classes of cancer patients based on Big Five personality dimensions and evaluated for differences in demographic and clinical characteristics, depression, anxiety, and cancer-related symptoms. Methods: Patients ( n  = 1248) with breast, gastrointestinal, gynecological, or lung cancer completed the Center for Epidemiological Studies-Depression scale, Spielberger State-Trait Anxiety Inventories, NEO-Five Factor Inventory (NEO-FFI), and Memorial Symptom Assessment Scale (MSAS). Latent class profile analysis of NEO-FFI scores was used to identify patient subgroups. Results: Three latent classes were identified. The "Distressed" class (14.3%) scored highest on neuroticism and lowest on extraversion, agreeableness, and conscientiousness. The "Resilient" class (31.9%) scored lowest on neuroticism and highest on extraversion, agreeableness, and conscientiousness. The "Normative" class (53.8%) was intermediate on all dimensions except openness. Compared to the Resilient class, patients in the Distressed class were younger, less educated, more likely to care for another adult, had more comorbidities, and exercised less. The three classes differed by performance status, marital and employment status, and income, but not by gender, time since diagnosis, or type of prior cancer treatment. The classes differed (Distressed > Normative > Resilient) in depression, anxiety, and cancer symptoms. Conclusions: Personality is associated with psychological and physical symptoms in cancer patients. Highlights: We identified three groups of cancer patients based on personality profiles. We named them "Normative" (54%), "Resilient" (32%), and "Distressed" (14%). The groups differed in levels of depressive and anxiety symptoms. The groups also differed in levels of cancer-related symptoms. Personality may affect psychological and physical symptoms during chemotherapy.